Pre-bout hypertension in the combat sports athlete: clearance recommendations - deWeber, K.; Ota, K. S.; Dye, C. (The Physician and Sportsmedicine, 2023)
Hypertension is one of the most prevalent medical disorders in the world and is associated with significant cerebrovascular and cardiovascular morbidity. Pre-bout blood pressure (BP) elevation is extremely common, and ringside physicians must accurately assess the accompanying risk of adverse cerebrovascular and cardiovascular events in the decision to allow participation in combat sports. It is strongly recommended that a ringside physician consider disqualifying a combat sports athlete with severe pre-bout hypertension (systolic BP =160 mm Hg and/or diastolic BP =100 mm Hg, or stage 2 hypertension in children when indexed by gender, age, and height) from that bout, if it persists despite rest and repeated measurement with accurate equipment. This recommendation is congruent with that of the American College of Sports Medicine, the American College of Cardiology, and the American Heart Association, which recommend non-clearance for sports or exercise testing when BP exceeds those thresholds. Severely elevated BP, as defined above, confers markedly increased risk of morbidity and mortality. Exercise further raises BP markedly. The combination of severely elevated blood pressure and cranial trauma during combat sports is a risk factor for intracranial hemorrhage with a direct impact on the morbidity and mortality associated with ringside combat sports events. Combat sports athletes with SBP =130 or DBP =90 - and their coaches and families, if available and the athlete consents - should be educated on the causes of hypertension, its acute and chronic risks, and the possible future implications for bout clearance, and the athletes should be referred for evaluation and management.